Integration of Qur'anic worldview with natural science: answering the long call for Islamic secondary schools = تكامل بين نظرية قرآنية وعلوم طبيعية : إجابة مكاملة الطويلة للمدرسة الإسلامية - Hassan, Nur Jannah (Department of Qur'an and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University, 2018)
Integration has been a key concern in the education of the ummah since the post-colonial period that have left Muslims with the legacy of a dichotomous education. Today, we see many Islamic schools with different modes of integration. But what constitutes as integration? How much have Muslims progressed towards true integration? This article presents a brief qualitative report on the findings from field researches that probed into samples of integration at 24 Islamic secondary schools in Malaysia and Indonesia (and surveys in Brunei, Singapore, Mindanao, Southern Thailand and Ontario) comparing with the ideal where integration constitutes an organic fusion between revealed and acquired knowledge. The article skims through the worldviews that have brought about natural science to its current plinth. It proposes a model for Islamic secondary education where natural sciences undergo a discreet but holistic reconstruction, redefinition and redirection from the framework of the Qur’ānic worldview.